2020
DOI: 10.1016/j.taap.2019.114875
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a phthalate metabolite mixture on antral follicle growth and sex steroid synthesis in mice

Abstract: Phthalates are used as solvents and plasticizers in a wide variety of consumer products. Most people are exposed to phthalates as parent compounds through ingestion, inhalation, and dermal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Additionally, DIP-group showed a significant decrease of BCL2 associated with a significant increase of AIFM1 and BCL2L10 if compared to C-group. This is consistent with a previous study, 20 which reported that the balance between pro- and anti-apoptotic factors did change in the ovary after phthalate exposure, depending on the concentration used; those findings may explain the increased apoptotic activity we noticed in the colon after DIP ingestion and provides a clue for the anti-apoptotic potential of FO.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, DIP-group showed a significant decrease of BCL2 associated with a significant increase of AIFM1 and BCL2L10 if compared to C-group. This is consistent with a previous study, 20 which reported that the balance between pro- and anti-apoptotic factors did change in the ovary after phthalate exposure, depending on the concentration used; those findings may explain the increased apoptotic activity we noticed in the colon after DIP ingestion and provides a clue for the anti-apoptotic potential of FO.…”
Section: Discussionsupporting
confidence: 93%
“…22,23 The MTT test is a colorimetric assay that is used to evaluate cellular metabolic activity, allowing the assessment of the effects of different doses of chemicals on cell viability, proliferation, and cytotoxicity. [24][25][26][27] In the 24-h MTT assay, the mixture decreased cell was more resistant to the effects of the mixture than the LNCaP cells, possibly due to its greater capacity for cell repair and defense, 28,29 resulting in fewer alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The MTT test is a colorimetric assay that is used to evaluate cellular metabolic activity, allowing the assessment of the effects of different doses of chemicals on cell viability, proliferation, and cytotoxicity 24–27 . In the 24‐h MTT assay, the mixture decreased cell viability in both LNCaP and PNT‐2 from the 4000 μmol/L dose onwards.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratory have shown that exposure to DBP alone 33 , a parent phthalate mixture of DEHP, DBP, diisobutyl phthalate (DiBP), benzyl butyl phthalate (BBzP), and DiNP 30 , and a phthalate metabolite mixture of monoethyl phthalate (MEP), mono(2-ethylhexyl) phthalate (MEHP), monobutyl phthalate (MBP), monoisobutyl phthalate (MiBP), monobenzyl phthalate (MBzP), and monoisononyl phthalate (MiBP) 44 disrupt the expression of genes involved in apoptotic and cell cycle pathways in the ovary. Thus, we examined whether DiNP exposure alters the expression of mRNAs for various cell cycle regulators as well as cell proliferation and apoptosis in the colon.…”
Section: Discussionmentioning
confidence: 99%